The role of science for conservation - Wolff, Matthias, 1955-; Gardener, Mark. (London ; New York : Routledge, 2012)
"The book aims at describing to a broad audience 50 years of research of Charles Darwin Foundation as part of the worldwide efforts in conservation science. A model case is presented showing how interdisciplinary work across a broad range of scientific disciplines (evolution science, taxonomy, botany, terrestrial and marine ecology, ecological restoration, fisheries science, oceanography, social and economic science) has contributed to the conservation and sustainable development of the Galapagos archipelago and to the advancement of science. The book describes the state-of-the-art knowledge on the Galapagos socio-ecosystem, presents modern modeling tools for the integration of information from diverse science disciplines and highlights contrasting viewpoints with regard to future scenarios for reconciling conservation with socio-economic development of the archipelago. The book is innovative in its multidisciplinary focus on conservation and in presenting up- to-date tools for scenario modeling. The book is structured into the following four chapters: The evolutionary context; biodiversity assessment and monitoring of change; a systemic approach: modeling and restoration; reconciliation of conservation with socio-economic development. Each chapter is comprised of several individual papers and ends with a chapter summary that highlights the main findings and conclusions. The book integrates the knowledge and reflections of 30 scientists, of which many have dedicated a substantial part of their professional life to the Galapagos archipelago, to the conservation of its biodiversity and to the sustainable management of its resources. The book can be considered a milestone on the way to the successful conservation and sustainable development of this unique world heritage"--
pt. I. The evolutionary context -- pt. II. Biodiversity assessment and monitoring of change -- pt. III. A systemic approach : modeling and restoration -- pt. IV. Reconciliation of conservation with socio-economic development.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nature conservation -- Galapagos Islands; Sustainable biodiversity -- Galapagos Islands; Restoration ecology -- Galapagos Islands; Sustainable development -- Research -- Galapagos Islands; Conservation biology -- Research -- Galapagos Islands; Evolution (Biology) -- Research -- Galapagos Islands; Natural history -- Galapagos Islands; Galapagos Islands -- Economic conditions; Electronic books